Cocontraction of internal and external oblique muscles during maximal strength tests in professional tennis players - Vera-Garcia, F. J.; Azorin-Picazo, F.; Moya-Ramón, M.; Moreno-Hernández, J. (Archivos de medicina del deporte, 2008)
Repetitive and quick flexion-extension and rotation activities, as serves or forehand and backhand strokes in tennis seem contributing factors to develop pelvic and spine disorders and pain. The aim of this study was to analyze the amplitude of the electromyography (EMG) of internal and external oblique (IO and EO, respectively) during six maximal strength tests that mimic the posture of the trunk and arms in different tennis strokes. Material and methods: Five professional male tennis players, without current back or shoulder pain, volunteered to take part in this study (higher ATP rankings: 50, 65, 161, 183 and 246; age = 26.2 ± 2.3 yr, height = 181.5 ± 3.4 cm, mass = 80.3 ± 4.9 kg). After warming-up, subjects were positioned in a sat posture, with the pelvis strapped, while holding a steel cable handle attached to a wall. Then, subjects pushed against the handle to produce their maximum isometric force. The cable was oriented in different directions in order to mimic three tennis techniques: service, one-handed stroke and two-handed stroke. Each technique was performed three times in both sides of the body (6 maximal tests x 3 trials = 18 trials). Superficial EMG (Muscle Tester ME6000, Mega Electronics Ltd.) was recorded bilaterally from IO and EO. The EMG signals were full wave rectified, averaged every 0.01 s, and then normalized to trunk maximal voluntary isometric contraction amplitudes (MVIC). Results: Table 1 shows the normalized maximum muscle activities for each of the maximal tests.